Pengembangan Kompetensi Menulis Puisi melalui Workshop Penulisan Puisi di Balikpapan - Ari Musdolifah; Nurliani Maulida; Ryan Angga Pratama (Abdimas Universal, 2023)
Writing skills are indispensable in life. Based on the genre, writing can be divided into two, namely fiction and nonfiction. Poetry is one of the nonfiction genres. Writing poetry is a complicated activity. It takes a variety of assignments and training to develop poetry writing skills.. This activity is based on the many obstacles of young people in Balikpapan when writing poetry. This activity is carried out in four stages, namely preparation, implementation by conducting counseling by providing material; understanding, types, structure, and constituent elements of poetry, as well as evaluation, and preparation of reports. The implementers of this activity are FKIP lecturers at Balikpapan University and the Balikpapan Junjung Nyawa community. This activity was carried out at the Klandasan Parking Building which is located at Jalan Jenderal Sudirman, No. 9, Klandasan Ulu, Balikpapan City, East Kalimantan. The result of this activity is that the young people of Balikpapan can create poetry in accordance with the rules of writing good and correct poetry.